2018
DOI: 10.1016/j.pbb.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to hypothermic and antinoceptive effects of ∆9-tetrahydrocannabinol (THC) vapor inhalation in rats

Abstract: Repeated daily THC inhalation induces tolerance in female and male rats, providing further validation of the vapor inhalation method for preclinical studies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
50
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 37 publications
10
50
2
Order By: Relevance
“…Due to reasonably frequent co-exposure of human cannabis users to nicotine (Cooper and Haney 2009;Eggers et al 2017;Ream et al 2008;Schauer et al 2017;Timberlake 2009), this study further determined the effects of co-exposure to THC and nicotine via vapor inhalation. Prior work with our inhalation model demonstrated consistent, dose-dependent hypothermic effects of THC inhalation and an inconsistent suppression of locomotor behavior in male and female Wistar, as well as male Sprague-Dawley, rats (Javadi-Paydar et al 2018a;Nguyen et al 2016b;Nguyen et al 2018). Parenteral injection of nicotine has previously been found to increase the hypothermia associated with injected THC (Pryor et al 1978;Valjent et al 2002), thus there was reason to expect similar effects in this model.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Due to reasonably frequent co-exposure of human cannabis users to nicotine (Cooper and Haney 2009;Eggers et al 2017;Ream et al 2008;Schauer et al 2017;Timberlake 2009), this study further determined the effects of co-exposure to THC and nicotine via vapor inhalation. Prior work with our inhalation model demonstrated consistent, dose-dependent hypothermic effects of THC inhalation and an inconsistent suppression of locomotor behavior in male and female Wistar, as well as male Sprague-Dawley, rats (Javadi-Paydar et al 2018a;Nguyen et al 2016b;Nguyen et al 2018). Parenteral injection of nicotine has previously been found to increase the hypothermia associated with injected THC (Pryor et al 1978;Valjent et al 2002), thus there was reason to expect similar effects in this model.…”
Section: Discussionsupporting
confidence: 53%
“…Injected nicotine has previously been shown to reduce body temperature and increase spontaneous locomotion in rats (Bryson et al 1981;Clemens et al 2009;Green et al 2003;Levin et al 2003), thus these measures were selected for initial validation. These have the additional advantages of supporting indirect crossdrug comparison with our prior reports on the effects of inhaled THC (Javadi-Paydar et al 2018a;Nguyen et al 2016b;Nguyen et al 2018) and psychomotor stimulants (Nguyen et al 2016a;Nguyen et al 2017). As in those prior studies, it was further important to contextualize some of the inhaled effects, including plasma nicotine and cotinine levels, with those produced by parenteral nicotine injection.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Analysis of each treatment day revealed that AM11101 increased 1-hr food intake on five of 7 days, whereas THC's orexigenic effect was limited to 2 days. While previous studies have shown that THC's behavioural and physiological effects can dissipate in as few as four daily injections (Jarbe & DiPatrizio, 2005;Nguyen et al, 2018), we saw no evidence of tolerance to the orexigenic effects of THC or AM11101 in our study.…”
Section: Discussioncontrasting
confidence: 93%
“…Recently, we began using ENDS to deliver vaporized drugs to rodents in standard housing chambers. This method has been used to administer vaporized Δ9-tetrahydrocannabinol (THC; Nguyen et al 2016aNguyen et al , 2018Javadi-Paydar et al 2018, opiates (Vendruscolo et al 2018), stimulants (Nguyen et al 2016b(Nguyen et al , 2017, nicotine (Javadi-Paydar et al 2019), or combinations of these drugs (Javadi-Paydar et al 2019). ENDS nicotine inhalation produces behavioral and physiological effects in rats, such as increases in spontaneous locomotor activity and decreases in body temperature (Javadi-Paydar et al 2019).…”
Section: Introductionmentioning
confidence: 99%